Kinetic Alfvén wave explanation of the Hall fields in magnetic reconnection. Issue 2 (25th January 2017) - Dai, Lei; Wang, Chi; Zhang, Yongcun; Lavraud, Benoit; Burch, James; Pollock, Craig; Torbert, Roy B.
Abstract: Magnetic reconnection is initiated in a small diffusion region but can drive global‐scale dynamics in Earth's magnetosphere, solar flares, and astrophysical systems. Understanding the processes at work in the diffusion region remains a main challenge in space plasma physics. Recent in situ observations from Magnetospheric Multiscale and Time History of Events and Macroscale Interactions during Substorms reveal that the electric field normal to the reconnection current layer, often called the Hall electric field ( E n ), is mainly balanced by the ion pressure gradient. Here we present theoretical explanations indicating that this observation fact is a manifestation of kinetic Alfvén waves (KAWs) physics. The ion pressure gradient represents the finite gyroradius effect of KAW, leading to ion intrusion across the magnetic field lines. Electrons stream along the magnetic field lines to track ions, resulting in field‐aligned currents and the associated pattern of the out‐of‐plane Hall magnetic field ( B m ). The ratio Δ E n /Δ B m is on the order of the Alfvén speed, as predicted by the KAW theory. The KAW physics further provides new perspectives on how ion intrusion may trigger electric fields suitable for reconnection to occur. Key Points: Hall electric field balanced by ion pressure gradient represents the finite ion gyroardius of kinetic Alfven waves KAW physics predicts a ratio of Hall fields ( E n / B m ) on the order of a few Alfven speed New perspetive on ion intrusion at magnetopause reconnection